Poly(ADP-ribose) Polymerase-1 Inhibition in Brain Endothelium Protects the Blood—Brain Barrier under Physiologic and Neuroinflammatory Conditions. Issue 1 (January 2015) - Rom, Slava; Zuluaga-Ramirez, Viviana; Dykstra, Holly; Reichenbach, Nancy L; Ramirez, Servio H; Persidsky, Yuri
Blood—brain barrier (BBB) dysfunction seen in neuroinflammation contributes to mortality and morbidity in multiple sclerosis, encephalitis, traumatic brain injury, and stroke. Identification of molecular targets maintaining barrier function is of clinical relevance. We used a novel in vivo model of localized aseptic meningitis where tumor necrosis factor alpha (TNFα) was introduced intracerebrally and surveyed cerebral vascular changes and leukocyte—endothelium interactions by intravital videomicroscopy. Poly(ADP-ribose) polymerase-1 (PARP) inhibition significantly reduced leukocyte adhesion to and migration across brain endothelium in cortical microvessels. PARP inactivation diminished BBB permeability in an in vivo model of systemic inflammation. PARP suppression in primary human brain microvascular endothelial cells (BMVEC), an in vitro model of BBB, enhanced barrier integrity and augmented expression of tight junction proteins. PARP inhibition in BMVEC diminished human monocyte adhesion to TNFα-activated BMVEC (up to 65%) and migration (80–100%) across BBB models. PARP suppression decreased expression of adhesion molecules and decreased activity of GTPases (controlling BBB integrity and monocyte migration across the BBB). PARP inhibitors down-regulated expression of inflammatory genes and dampened secretion of pro-inflammatory factors increased by TNFα in BMVEC. These results point to PARP suppression as a novel approach to BBB protection in the setting of endothelial dysfunction caused by inflammation.